Heterosis and reciprocal effects on productive and reproductive performance in F1 generations of Fayoumi x White leghorn and Koekoek x White leghorn chickens - Balcha, Kasaye Assefa; Senbeta , Ewonetu Kebede; Megersa, Ashenafi Getachew (Acta Scientiarum. Animal Sciences, 2024)
This study evaluated heterosis and reciprocal effects in across of White Leghorn with Fayoumi, White Leghorn with Koekoek in comparison to their pure line breeds for the productive and reproductive traits. Data were purposively collected from 357 layers based on their genetic groups and each genotype was reared in three replicates on a deep litter system from 20-72 weeks. Results showed that genotype groups were found to have no significant differences (p > 0.05) for age at first egg (AFE) and hen- housed egg production (HHEP). Purebred Koekoek and crossbred of male White Leghorn and female Koekoek were superior for body weight at first egg (BWAFE). Purebred Fayoumi has exhibited the least values for egg number. Purebred White Leghorn was the best by their feed conversion ratio. Effects of heterosis were non-significant (p > 0.05) for AFE and BWAFE, and hen-housed egg production. A negative heterosis percentage was noted for AFE in all crossbred genotypes. Crossing between male Koekoek and female White Leghorn gave the highest heterosis effect for feed intake while crossing between male White Leghorn and female Fayoumi gave the highest estimates of heterosis for total egg number per hen. The main crossbred between male White Leghorn and female Fayoumi hybrids outperformed in AFE and HHEP while the main crossbred between male White Leghorn and female Koekoek outperformed in BWAFE and HHEP. On the contrary, reciprocal crossbreds between male Fayoumi and female White Leghorn and male Koekoek and female White Leghorn had higher feed intake and better feed conversion ratio.